An Introduction to Intelligence Engineering: Operating Beyond the Conventional - Svendsen, Adam (Cranfield University, 2020)
Contemporary defence and security enterprise efforts can be viably improved. With an overarching focus on ‘ways’, ‘means’, up and across to realising operational and strategic-ranging ‘ends’, this presentation advances a substantially-structured, multi-scaler ‘Intelligence Engineering’ (IE)-based framework and ‘step-by-step’ toolbox useful for both deployment and employment for a multitude of purposes - essentially whatever is to be accomplished. As the presentation goes on to reveal, the IE framework can contribute towards helping progress several tasks, such as including -but not limited to -the work of interest to several different high-level leaders and policy- to decision-makers and other share-/ stakeholders, end-users, customers or clients. Both ‘situational awareness’ to deeper-ranging ‘contextualisation’ assistance value is offered. The different process ‘steps’ cover diverse areas such as, inter alia: ‘focus/topic selection’ through to the fashioning of ‘signiﬁer node(s)’ for helping in decision-making both now and into the future. Concluding, the presentation highlights that the entire process involved facilitates: (i) greater risk appreciation; and then (ii) subsequent risk management; as well as even advancing (iii) risk engineering to resilience qualities. This is in overall defence and security enterprises and endeavours (however precisely they might be deﬁned or determined) during an era when much uncertainty is encountered.
Keywords: 'Intelligence engineering'; 'Intelligence analysis'; 'Situational awareness'; 'DSDS19'; 'DSDS19 Digital Image'; 'Decision Support and Group Support Systems'